2010
DOI: 10.14214/sf.146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil preparation method on economic result of Norway spruce regeneration chain

Abstract: Economic result of forest regeneration chains, based either on spot mounding or on disc trenching and planting of Norway spruce (Picea abies [L.] Karst.) seedlings, were clarified and compared to each other. First, effects of soil preparation method on early development of Norway spruce stands were measured from field experiments. Second, the effects of soil preparation method on stand level management programs were modelled. The modelling was based on growth simulation and investment calculations. The soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Study in central Finland found that it has been present mainly on areas with ditch mounded and inverted soil (Heiskanen et al, 2013). Similar to our results, superior height growth of trees planted on mounds had been found also in numerous studies in Sweden and Finland (Saarinen, 2007;Lehtosalo et al, 2010;Uotila et al, 2010;Hallsby & Örlander, 2013). Even so the reported (Ör-lander et al, 1990, 1998) differences in tree height between the soil preparation methods were smaller than those found in our study, presumably due to slower growth in more northern climatic conditions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Study in central Finland found that it has been present mainly on areas with ditch mounded and inverted soil (Heiskanen et al, 2013). Similar to our results, superior height growth of trees planted on mounds had been found also in numerous studies in Sweden and Finland (Saarinen, 2007;Lehtosalo et al, 2010;Uotila et al, 2010;Hallsby & Örlander, 2013). Even so the reported (Ör-lander et al, 1990, 1998) differences in tree height between the soil preparation methods were smaller than those found in our study, presumably due to slower growth in more northern climatic conditions.…”
Section: Resultssupporting
confidence: 91%
“…forest types, however, these differences were non-signifi cant (p = 0.05 and p = 0.53, respectively). Differences were more pronounced, when trees growing on mounds were compared with those growing in unprepared soil: in these circumstances one third of trees in Oxalidosa forest type and as much as two thirds in Myrtilloso-polytrichosa forest type were lower than 1.5 m. Similar infl uence of soil preparation method on tree height distribution in young Norway spruce stand was found also in Finland (Uotila et al, 2010).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…For example, the number of prepared spots is the main CSF in soil preparation because it provides the foundation for planting and future performance of the seedling. High quality sites are for instance characterized by approximately 2000 mounds ha -1 that are large enough for planters to plant seedlings correctly but not so large as to provide substrate for opportunistic broadleaf trees (Uotila et al 2010). Planting work is evaluated in terms of the proportion of seedlings that are planted correctly, i.e., stems anchored well in the soil and their roots reaching nutritious humus layer when possible (Long 1991;Luoranen and Viiri 2016).…”
Section: Introductionmentioning
confidence: 99%